GC–MS study of compounds isolated from Coffea arabica flowers by different extraction techniques (2013)
Headspace (HS), extractive, and distillative methods were employed to isolate volatile and semivolatile compounds from fresh Coffea arabica flowers. Static HS solid-phase microextraction (HS-SPME), microwave-assisted HS-SPME (MW-HS-SPME) with simultaneous hydrodistillation, and extraction with hexane or supercritical CO2-isolated mixtures in which around 150 different chemical substances were identified or tentatively identified by GC–MS analysis. n-Pentadecane (20–37% relative peak area, RPA) was the most abundant compound in the HS fractions from fresh flowers, followed by 8-heptadecene (8–20% RPA) and geraniol (6–14% RPA). Hydrocarbons (mostly C13–C30 paraffins) were the predominant compound class in all the sorptive extractions (HS-SPME, MW-HS-SPME, distillate), followed by terpenoids or oxygenated compounds (which varied with the isolation technique). Caffeine, a distinctive component of coffee fruits and beans, was also found in relatively high amounts in the supercritical CO2 extract of C. arabica flowers.